(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Bawang dayak (Eleutherine americana (Aubl) Merr.) ethanol extract had been known to have excellent antioxidant activity that has the potential to be developed into a nanoparticle delivery systems. This study aims to determine the effect of varying concentrations of chitosan - tripolyphosphate (TPP) to the physical characteristics of nanoparticles. Bawang dayak extract formulated in the form of nanoparticles with an ionic gelation method and and using polymers chitosan - tripolyphospate varying concentration as 0.5% : 0.5% (F1), 0.75% : 0.5% (F2), and 1% : 0.5% (F3). The measured parameters were determinating particle size and polydispersity index using particle size analyzer, observation of particle morph using scanning electron microscopy, measurement of entrapment efficiency and dissolution in vitro. The result showed that the average size of nanoparticle F1, F2, and F3 respectively is 256.30 nm, 376 nm and 419.18 nm with entrapment efficiency respectively is 69.54% (F1), 77.51% (F2) and 79.79% (F3) with a relatively homogenous size distribution and entrapment efficiencies respectively is 69.54%, 77.51% and 79.79%. Observation of morphology of the nanoparticles shows the particle shape is almost sphere (spherical) with a rough surface. The profile of drug release from the nanoparticles F1, F2, and F3 in 8 hours respectively is 71.19% (F1), 74.97% (F2) and 80.55% (F3). Based on this study, it was concluded that the etanol extract of bawang dayak can be formulated into nanoparticles with different physical characteristics based on the ratio of polymer chitosan and tripolyphosphate used.